Transcriptomic studies in malaria – a paradigm for investigation of systemic host-pathogen interactions - Lee,HJ; Georgiadou,A; Otto,T; Levin,M; Coin,L; Conway,D; Cunnington,A (Microbiology and Molecular Biology Reviews, 2018)
Transcriptomics, the analysis of genome-wide RNA expression, is a common approach to investigate host and pathogen processes in infectious diseases. Technical and bioinformatic advances have permitted increasingly thorough analysis of the association of RNA expression with fundamental biology, immunity, pathogenesis, diagnosis, and prognosis. Transcriptomic approaches can now be used to realize a previously unattainable goal, simultaneous study of RNA expression in host and pathogen, in order to better understand their interactions. This exciting prospect is not without challenges, especially as focus moves from interactions in vitro under tightly controlled conditions to tissue-and systemic-level interactions in animal models and natural and experimental infections in humans. Here we review the contribution of transcriptomic studies to the understanding of malaria, a parasitic disease which has exerted a major influence on human evolution and continues to cause a huge global burden of disease. We consider malaria as a paradigm for transcriptomic assessment of systemic host-pathogen interaction in humans, because much of the direct host-pathogen interaction occurs within the blood–a readily sampled compartment of the body. We illustrate lessons learned from transcriptomic studies of malaria, and how these may guide studies of host-pathogen interaction in other infectious diseases. We propose that the potential of transcriptomic studies to improve understanding of malaria as a disease remains partly untapped because of limitations in study design rather than as a consequence of technological constraints. Further advances will require integration of transcriptomic data with analytical approaches from other scientific disciplines including epidemiology and mathematical modelling.